Long-term outcome in tetanus cohort: 04TS - Thwaites, L; Duoc, N V T; Trung, T N (University of Oxford, 2021)
This is a data set from a clinical observation study. The data was manually entered from case record forms to a specific database. This dataset is from the exported data.